Kingdom of the Netherlands : Netherlands; 2008 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Kingdom of the Netherlands; Netherlands. (IMF Staff Country Reports; Country Report, 2008)
Strong macroeconomic foundations have so far largely shielded the Netherlands from recent financial turbulence. Despite a tightening labor market, inflation remains subdued. Employment has grown 1u-1 1\2 percent in 2007, on par with the rest of the Euro area. The external current account surplus remains large, and various approaches suggest that Dutch competitiveness is satisfactory. Fiscal performance, while staying strong, has been mildly procyclical since 2007. Long-term fiscal sustainability remains elusive, owing to population aging and its attendant budgetary costs.